2000
DOI: 10.1097/00006123-200006000-00003
|View full text |Cite
|
Sign up to set email alerts
|

What Percentage of Surgically Clipped Intracranial Aneurysms Have Residual Necks?

Abstract: The lack of information regarding both the frequency of residual filling or regrowth and long-term angiographic follow-up of patients with surgically treated aneurysms makes meaningful comparison between surgical treatments and new treatment methods for intracranial aneurysms difficult or impossible. Detailed analysis with high-quality angiography should be performed to determine the success of surgical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
60
0
8

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(71 citation statements)
references
References 12 publications
3
60
0
8
Order By: Relevance
“…Except for the results of postoperative cerebral angiography, these were relatively high rates compared with previous incidences, 5,8,18,24) and may be attributed to various factors. First, in the present study, a small residual neck that may have been previously ignored was included as an aneurysm remnant.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Except for the results of postoperative cerebral angiography, these were relatively high rates compared with previous incidences, 5,8,18,24) and may be attributed to various factors. First, in the present study, a small residual neck that may have been previously ignored was included as an aneurysm remnant.…”
Section: Discussionmentioning
confidence: 57%
“…24) Postoperative angiography after clipping of cerebral aneurysms showed that the incidence of residual aneurysms was 2.3% to 14%. 24) Aneurysm remnants after clipping may regrow and lead to recurrent symptoms of hemorrhage or mass effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 Long-term follow-up has also revealed new aneurysms in 8% of patients after subarachnoid hemorrhage, 12,13 indicating the importance of postoperative follow-up. To date, postoperative status has usually been evaluated by using DSA.…”
Section: Discussionmentioning
confidence: 99%
“…Na série de 169 casos publicada por Cognard et al 15 , em 44% deles foi verificada oclusão sub-total ou incompleta, 18 deles necessitando de tratamento endovascular complementar. A análise destas séries é de grande importância na comparação dos resultados obtidos após clipagem cirúrgica 16,17 .…”
Section: Discussionunclassified